Mass-scalable synthesis of 3D porous germanium–carbon composite particles as an ultra-high rate anode for lithium ion batteries. Issue 12 (25th August 2015) - Ngo, Duc Tung; Le, Hang T. T.; Kim, Chanhoon; Lee, Jae-Young; Fisher, John G.; Kim, Il-Doo; Park, Chan-Jin
Abstract : A novel, facile synthetic route has been proposed to prepare a 3D nanoarchitecture of Ge coated with carbon (3D-Ge/C) via carbothermal reduction. Abstract : Electrode materials with three-dimensional (3D) mesoporous structures possess superior features, such as a shortened solid-phase lithium diffusion distance, a large pore volume, full lithium ion accessibility, and a high specific area, which can facilitate fast lithium ion transport and electron transfer between solid/electrolyte interfaces. In this work, we introduce a facile synthesis route for the preparation of a 3D nanoarchitecture of Ge coated with carbon (3D-Ge/C) via a carbothermal reduction method in an inert atmosphere. 3D-Ge/C showed excellent cyclability: almost 86.8% capacity retention, corresponding to a charge capacity of 1216 mA h g −1 even after 1000 cycles at a 2C-rate. Surprisingly, the high average reversible capacity of 1122 mA h g −1 was maintained at a high charge rate of 100C (160 A g −1 ). Even at an ultrahigh charge rate of 400C (640 A g −1 ), an average capacity of 429 mA h g −1 was attained. Further, the full cell composed of a 3D-Ge/C anode and an LiCoO2 cathode exhibited excellent rate capability and cyclability with 94.7% capacity retention over 50 cycles. 3D-Ge/C, which offers a high energy density like batteries as well as a high power density like supercapacitors, is expected to be used in a wide range of electrochemical devices.